In memoriam - CPH 47(1-2), (Czasopismo Prawno-Historyczne, 1995)
Witold Maisel 1914-1993 (Jacek Sobczak) ... 299 Irena Malinowska-Kwiatkowska 1925-1994 (Kazimierz Baran) ... 303 Jan Wąsicki 1921-1995 (Krystyna Sikorska-Dzięgielewska) ... 305